Inducible and reversible gene silencing by stable integration of an shRNA-encoding lentivirus in transgenic rats - Herold, Marco J. (National Academy of Sciences, 2008)
Currently, tools to generate loss-of-function mutations in rats are limited. Therefore, we have developed a lentiviral single-vector system for the temporal control of ubiquitous shRNA expression. Here, we report transgenic rats carrying an insulin receptor-specific shRNA transcribed from a regulatable promoter and identified by concomitant EGFP expression. In the absence of the inducer doxycycline (Dox), we observed no siRNA expression. However, Dox treatment at very low concentrations led to a rapid induction of the siRNA and ablation of INSR protein expression. As anticipated, blood glucose levels increased, whereas insulin signaling and glucose regulation were impaired. Importantly, this phenotype was reversible (i.e., discontinuation of Dox treatment led to INSR re-expression and remission of diabetes symptoms). The lentiviral system offers a simple tool for reversible gene ablation in the rat and can be used for other species that cannot be manipulated by conventional recombination techniques.